2017
DOI: 10.1111/jdv.14221
|View full text |Cite
|
Sign up to set email alerts
|

Factors linked to disease severity and time to remission in patients with chronic spontaneous urticaria

Abstract: Biomarkers useful for the evaluation and management of patients with chronic spontaneous urticaria (CSU) are not currently available. A review of various clinical and laboratory markers that have been studied to assess their value for determining the severity or predicting the evolution of disease in adult patients with CSU was carried out. A search of the medical literature on PubMed and MEDLINE including the terms urticaria, chronic urticaria, chronic idiopathic urticaria, CSU, severity, prognosis and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 87 publications
2
48
1
3
Order By: Relevance
“…Patients who experience CSU as concurrent hives and angioedema often experience a longer duration of disease than patients who experience only hives . Angioedema may be disfiguring or painful, may limit daily activities and may have a significant impact on quality of life .…”
Section: Introductionmentioning
confidence: 99%
“…Patients who experience CSU as concurrent hives and angioedema often experience a longer duration of disease than patients who experience only hives . Angioedema may be disfiguring or painful, may limit daily activities and may have a significant impact on quality of life .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the common manifestations including itch, wheals and/or angioedema that last for more than 6 weeks, these entities are triggered by different stimuli and display different pathogenic mechanisms [1]. Furthermore, CIndU has been demonstrated to be a predictor of severe CSU [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies pointed out that mast cells and basophils play significant roles in the pathogenesis of CSU . For instance, it has been reported that the coagulation system and complement system participate in the mast cell activation in CSU patients . C‐reactive protein (CRP), encoded by the CRP gene, is greatly increased during infection, acute injury and autoimmune‐related diseases .…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] For instance, it has been reported that the coagulation system and complement system participate in the mast cell activation in CSU patients. [15,16] C-reactive protein (CRP), encoded by the CRP gene, is greatly increased during infection, acute injury and autoimmune-related diseases. [17] CRP is regarded as an acute phase protein (APP) in the course of mast cell degranulation and complement system activation in the coagulation system.…”
Section: Introductionmentioning
confidence: 99%